1999
DOI: 10.1080/10428199909169632
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-I Induced Intestinal Lymphoma

Abstract: We document an unusual case of HTLV-I positive adult T-cell leukaemia lymphoma (ATLL) in a 25 year old Chilean patient who presented with primary small intestinal involvement and during evolution developed a leukaemic phase. Duodenal biopsy showed infiltration by pleomorphic lymphoid cells with a CD45RO+ CD20- phenotype. Circulating lymphocytes had a convoluted nucleus and displayed a mature T-cell phenotype: CD2+, CD3+, CD4+, CD8-, CD25+, HLA-Dr+. HTLV-I serology was positive and HTLV-I retroviral sequences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Finally, 90 articles were chosen including 940 ATL reported cases; 24 papers were found in the Caribbean, 15,24,25,28–48 two in Central America (Table 2) 49,50 and 64 in South America (Table 3). 9,16,51…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 90 articles were chosen including 940 ATL reported cases; 24 papers were found in the Caribbean, 15,24,25,28–48 two in Central America (Table 2) 49,50 and 64 in South America (Table 3). 9,16,51…”
Section: Resultsmentioning
confidence: 99%
“…86 In Chile, up till 2003, seven articles were published. [88][89][90][91][92][93][94] In one of them, ATL was shown as the most frequent disease (48%) among 23 T-cell mature leukemias/lymphomas. In this study, serology for HTLV-1 was only performed in indicated cases.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an HTLV endemic country, Peru reports large cohorts of TSP/HAM reflecting a common disease [452][453][454][455], and also cases in which HTLV infection correlates with infective dermatitis [456], including children in which neurological disorders co-exists with infective dermatitis [457] and Strongyloides stercoralis [458,459]. Fifty-four cases of ATLL have been reported from Chile [266][267][268][269][270][271][272]275]. Highlights are the early presentation, with medians of 50 yrs and 51 yrs for the largest cohorts [266,268], and an onset concomitant with or proceeded by TSP/HAM.…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 99%
“…Therefore, the patient's diagnosis was stage IIE (Lugano classification) small-bowel adult T-cell leukemia/lymphoma (ATLL) accompanied by gastric AL amyloidosis. Although systemic ATLL often involves the small bowel [1 -3], primary small-bowel ATLL is extremely rare [4,5]. Endoscopic findings of small-bowel involvement with ATLL have included multiple polypoid or reddish elevated lesions [2,3].…”
mentioning
confidence: 99%